2006
DOI: 10.1585/pfr.1.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resonant Magnetic Fluctuations on Plasma Confinement in Current Carrying high-β Plasmas of LHD

Abstract: The effects of resonant magnetic fluctuations on plasma confinement have been investigated in current carrying high-β plasmas in magnetic hill configurations of the Large Helical Device. The m/n= 2/1 mode excited in core region was dominantly observed in the unstable configuration as predicted by linear theory on ideal instability, and the plasma current decreasing magnetic shear enhances the mode activity. The disappearance of the m/n = 2/1 mode was observed with an increase in plasma current, and then the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…11 And a beta collapse and the recover of the confinement performance are observed in the unfavorable configuration with the fairly high magnetic hill due to the interchange type instability. 12,13 The collapse resembles the internal disruption phenomena in the Heliotron-E, and the instabilities radial mode width is predicted quite large according to a linear stability analysis. 14 In the LHD experiment to extend the beta regime to the reactor-relevant high-beta plasmas, the increase of the neutral beam injection (NBI) heating power and=or the optimization of the magnetic configuration enable the production and the maintainment of the 5% volume averaged toroidal beta value for long time with $100 times of the energy confinement time without disruptive phenomena.…”
Section: Introductionmentioning
confidence: 90%
“…11 And a beta collapse and the recover of the confinement performance are observed in the unfavorable configuration with the fairly high magnetic hill due to the interchange type instability. 12,13 The collapse resembles the internal disruption phenomena in the Heliotron-E, and the instabilities radial mode width is predicted quite large according to a linear stability analysis. 14 In the LHD experiment to extend the beta regime to the reactor-relevant high-beta plasmas, the increase of the neutral beam injection (NBI) heating power and=or the optimization of the magnetic configuration enable the production and the maintainment of the 5% volume averaged toroidal beta value for long time with $100 times of the energy confinement time without disruptive phenomena.…”
Section: Introductionmentioning
confidence: 90%
“…4). In the LHD, it has been frequently observed that m/n = 2/1 magnetic fluctuations can cause local flattening in the electron temperature profile at its resonant position [9]. It is also possible to generate this flattening artificially using resonant magnetic perturbation coils placed in the LHD [10].…”
Section: Rotating Magnetic Structure and The Temperature Fluctuationmentioning
confidence: 99%
“…Constraints on the beta value β and its local gradient dβ/dρ at ρ = 0.5 (ρ: normalized minor radius) because of the onset of magnetic fluctuations caused by the m/n = 2/1 unstable mode (m: poloidal and n: toroidal mode numbers) as a dominant component were observed in the LHD [17,18]. Stabilization of the m/n = 2/1 mode by eliminating the ι/2π = 0.5 surface, resulting in the improvement of β by more than 30%, has been confirmed [17]. The discharges described in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The discharges described in Refs. [17] and [18] were performed with a magnetic field of 0.5 T for a high-β experiment, and the ι/2π = 0.5 surface was eliminated using a large cocurrent drive with tangential neutral beam injection. However, controlling the ι-profile by ECCD would improve plasma performance and provide experimental flexibility in discharges with higher magnetic fields.…”
Section: Introductionmentioning
confidence: 99%